A randomized controlled trial testing the efficacy of a brief cannabis universal prevention program among adolescents in primary care. (12th February 2014) - Walton, Maureen A.; Resko, Stella; Barry, Kristen L.; Chermack, Stephen T.; Zucker, Robert A.; Zimmerman, Marc A.; Booth, Brenda M.; Blow, Frederic C.
Abstract Aims To examine the efficacy of a brief intervention delivered by a therapist (TBI) or a computer (CBI) in preventing cannabis use among adolescents in urban primary care clinics. Design A randomized controlled trial comparing: CBI and TBI versus control. Setting Urban primary care clinics in the United States. Participants Research staff recruited 714 adolescents (aged 12–18 years) who reported no life‐time cannabis use on a screening survey for this study, which included a baseline survey, randomization (stratified by gender and grade) to conditions (control; CBI; TBI) and 3‐, 6‐ and 12‐month assessments. Measurements Using an intent‐to‐treat approach, primary outcomes were cannabis use (any, frequency); secondary outcomes included frequency of other drug use, severity of alcohol use and frequency of delinquency (among 85% completing follow‐ups). Findings Compared with controls, CBI participants had significantly lower rates of any cannabis use over 12 months (24.16%, 16.82%, respectively, P < 0.05), frequency of cannabis use at 3 and 6 months (P < 0.05) and other drug use at 3 months (P < 0.01). Compared with controls, TBI participants did not differ in cannabis use or frequency, but had significantly less other drug use at 3 months (P < 0.05), alcohol use at 6 months (P < 0.01) and delinquency at 3 months (P < 0.01). Conclusions Among adolescents in urban primary care in the United States, a computer brief intervention appeared to prevent and reduce cannabis use. Both computer and therapist delivered brief interventions appeared to have small effects in reducing other risk behaviors, but these dissipated over time.